2015
DOI: 10.1007/s13311-015-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Cannabidiol in Neurological Disorders

Abstract: Cannabis has a long history of anecdotal medicinal use and limited licensed medicinal use. Until recently, alleged clinical effects from anecdotal reports and the use of licensed cannabinoid medicines are most likely mediated by tetrahydrocannabinol by virtue of: 1) this cannabinoid being present in the most significant quantities in these preparations; and b) the proportion:potency relationship between tetrahydrocannabinol and other plant cannabinoids derived from cannabis. However, there has recently been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
344
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 462 publications
(359 citation statements)
references
References 269 publications
(406 reference statements)
3
344
0
12
Order By: Relevance
“…Results were obtained using the keywords “CB1R,” “CB2R,” “cannabinoid”, “cannabidiol”, “THC”/“Tetrahydrocannabinol”, “anandamide”, “2-AG”, “FAAH”/“Fatty acid amide hydrolase”, and “MAG lipase” plus the terms “seizures,” “epilepsy,” “epileptogenesis,” and “neuroprotection.” We excluded primarily in vitro studies and clinical studies in humans (clinical trials, case reports, observational studies). Studies were evaluated based on their scientific rigor and use of physiologically relevant drug concentrations to in vivo studies [13]. Summary details of all studies examined in the present review are presented in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Results were obtained using the keywords “CB1R,” “CB2R,” “cannabinoid”, “cannabidiol”, “THC”/“Tetrahydrocannabinol”, “anandamide”, “2-AG”, “FAAH”/“Fatty acid amide hydrolase”, and “MAG lipase” plus the terms “seizures,” “epilepsy,” “epileptogenesis,” and “neuroprotection.” We excluded primarily in vitro studies and clinical studies in humans (clinical trials, case reports, observational studies). Studies were evaluated based on their scientific rigor and use of physiologically relevant drug concentrations to in vivo studies [13]. Summary details of all studies examined in the present review are presented in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been suggested that cannabidiol targets GPR55 and GPR18 receptors, further subtypes of transient receptor potential receptors (TRPV2, TRPM8, TRPA1), α3 glycine receptors, adenosine receptors, μ and δ opioid receptors, nicotinic acetylcholine receptors, enzymes of the arachidonic acid cascade, ion channels like voltage-gated calcium channels or mitochondrial Na + /Ca 2+ exchange, nitric oxide signaling and inflammatory cytokines (McPartland et al, 2014; Ibeas Bih et al, 2015). To date, the antipsychotic properties of cannabidiol cannot be directly linked to these possible targets.…”
Section: Cannabidiol: Potential Mechanism Of Actionmentioning
confidence: 99%
“…One particular area of recent interest to researchers and clinicians has been the potential use of non‐psychoactive phytocannabinoids such as http://www.guidetopharmacology.org/GRAC/LigandDisplayForward?ligandId=4150) or its analogue cannabidivarin, also known as GWP42006 (Hill et al, 2012a; Bialer et al, 2015), in the treatment of epilepsy, particularly the more refractory, drug‐resistant forms (Ibeas Bih et al, 2015; Devinsky et al, 2017; Gaston and Friedman, 2017). …”
Section: Introductionmentioning
confidence: 99%